Post-Surgical Central Nervous System Infections in the Era of Multidrug Antibiotic Resistance in Greece—A Single-Center Experience of a Decade - Konstantinos Markakis; Konstantina Kapiki; Angela Ava Arbelle Edric; Asimina Aphrodite Pappas; Georgios Feretos; Sideris Nanoudis; Dimitrios Pilalas; Theodoros Michailidis; Efthymia Protonotariou; Lemonia Skoura; Nikolaos Foroglou; Symeon Metallidis; et al. (Pathogens)
Post-surgical central nervous system infections (PCNSIs) are a major cause of morbidity, poor functional outcomes and mortality in neurosurgical patients. These infections complicate operations of the CNS or are related to the use of neurosurgical devices or drainage catheters. Gram-negative bacteria, with multiple resistance patterns, are often isolated and these infections are difficult to treat, due to suboptimal antibiotic therapeutic levels in the cerebrospinal fluid (CSF). This is a retrospective study of PCNSIs between 2014 and 2024 in a single center of a tertiary hospital in Thessaloniki, Greece. Out of 2401 neurosurgical procedures, forty-one were complicated by PCNSIs, yielding a total PCNSI prevalence of 1.7%. Thirty-five involved cases with positive CSF culture. The most common interventions were craniotomies for the resection of tumors or other lesions (30.1%). Most cases referred to an EVD infection. Acinetobacter baumannii was the most commonly isolated pathogen (34.1%), followed by coagulase-negative Staphylococcus (22%) and Pseudomonas spp. (14.6%). Colistin and tigecycline were the most prescribed combination regimens. The median time to the first positive CSF culture postoperatively was 11 days (IQR 18 days). Empirical antibiotic treatment was adequate in 26 (63.4%) cases. The mortality rate among these patients was 65.7%. Survivors were significantly younger than non-survivors (p < 0.01) and had a shorter ICU length of stay (p < 0.01). The type of infection, time to infection onset, isolated pathogen, susceptibility to the empirical treatment and Charlson Comorbidity Index did not differ between the two groups. The mortality rate remains high in patients with PCNSIs. An integrated approach including surgical source control, supportive care, combination antimicrobial therapy and subsequent rehabilitation are mandatory to achieve treatment success and neurological convalescence.